Issues of Forming Ethnocultural Competence in The Harmony of National and Global Values - Isomiddinov Asliddin (Next Scientists International Journal JSSHRF, 2026)
The formation of ethnocultural competence has become one of the most significant tasks of contemporary education in the context of globalization, increasing intercultural interaction, and the transformation of social values. Modern students are expected not only to preserve their national identity and respect their own cultural heritage, but also to understand global values, engage in intercultural dialogue, and participate constructively in a multicultural world. This article examines the issues of forming ethnocultural competence in the harmony of national and global values from theoretical and pedagogical perspectives. The study analyzes the conceptual essence of ethnocultural competence, reveals its structural components, and identifies the pedagogical conditions necessary for its development in educational practice. Special attention is given to the interrelationship between national identity, cultural memory, tolerance, global citizenship, and value-based education. The article is based on theoretical analysis of pedagogical, cultural, philosophical, and psychological literature related to competence-based education, intercultural communication, ethnopedagogy, and value formation. The results of the study show that ethnocultural competence develops most effectively when national values are not isolated from global civilizational principles but harmonized with them through educational content, communication, and reflective activity. The study also demonstrates that the pedagogical process of developing ethnocultural competence requires integration of cognitive, emotional, behavioral, and axiological components. The findings confirm that the balance between national and global values supports students’ cultural self-awareness, social adaptability, intercultural respect, and civic maturity. The article concludes that the formation of ethnocultural competence is a complex and continuous pedagogical process that must be based on dialogue, cultural continuity, ethical reflection, and learner-centered educational strategies.